Resources Indexation-Based E-Learning System - Azzi, Ibtissam; Radouane, Abdelhay; Jeghal, Adil; Tairi, Hamid (Transactions on Engineering and Computing Sciences, 2017)
We propose in this article a study that illustrates the techniques used to represent the educational objects which serve to facilitate their reuse. We will enrich this study by taking into account the semantics of the contents of the learning objects while including the metadata as parameters of indexing. Another contribution of our study concerns the fact that this indexation relies on ontologies which allow a better semantic representation and facilitate communication between the machine and the users. On the other hand, we will discuss the current standards of indexing while discussing the cases of their use to try to extend the use of these standards in other situations requiring the indexing of resources in E -Learning systems.